Influence of film thickness on the structural, electrical and photoluminescence properties of vacuum deposited Alq(3) thin films on c-silicon substrate - Koay, J.Y.; Sharif K., A.M.; Rahman, S.A. (2009)
In this work. the influence of film thickness on the structural, electrical and photoluminescence (PL) properties of tris (8-hydroxyquinoline) aluminum (Alq(3)) films prepared by vacuum evaporation technique on crystal silicon (c-Si) substrate were studied. Fourier transform infrared (FTIR) spectroscopy. current-voltage (I-V), capacitance-voltage (C-V) and PL spectroscopy measurements were done to investigate these properties. The results demonstrated that the molecular organization of the deposited film was not affected by the film thickness. The PL emission energy and intensity increased with increase in film thickness. The results showed that the turn-on voltage (V-on) and transition voltage (V-T) were also dependent on the film thickness. (C) 2009 Published by Elsevier B.V.